Een bijzondere aankoop voor de KB: Huddes Specilla circularia - van Delft, Marieke (Studium, 2018)
In this article, the acquisition by the KB | National Library of the Netherlands is discussed of the only known printed copy of the book Specilla circularia, written by Johannes Hudde in 1656. The existence of this small but innovative booklet on the optical properties of telescope lenses was only known from contemporary scholarly correspondence. The content was unknown for a long time, but in 1995 two manuscripts revealing the text of Hudde’s Specilla circularia were discovered and subsequently pub- lished. In 2016 an extremely rare printed copy of Hudde’s booklet surfaced in an auction at the London department of Christies. Research by the auctioneer (and confirmed by other scholars), showed that this copy probably came from the library of Gerard Meerman, auctioned in The Hague in 1824.The extreme rarity of the booklet, its provenance and its contents led to the idea that the KB | National Library of the Netherlands would be the appropriate place for this booklet, written by a Dutch math- ematical heavyweight. After all, the KB houses an important Spinoza collection and a major collection of books written by Hudde’s contemporaties. Thus the KB attempted to acquire the Specilla circulariaand this proved successful: Hudde’s printed leaflet is now one of the highlights of this library.